2019
DOI: 10.1186/s12889-019-7831-9
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness, suitability, and sustainability of non-pharmacological methods of managing pain in community-dwelling older adults: a systematic review

Abstract: BackgroundPain is common in older adults. To maintain their quality of life and promote healthy ageing in the community, it is important to lower their pain levels. Pharmacological pain management has been shown to be effective in older adults. However, as drugs can have various side effects, non-pharmacological pain management is preferred for community-dwelling older adults. This systematic review evaluates the effectiveness, suitability, and sustainability of non-pharmacological pain management intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 42 publications
0
27
0
6
Order By: Relevance
“…There has been an increased in the use of non-drugs treatment for the participants in our study. A systematic review from Tang et al (24). suggests that non-pharmacological interventions are suitable and sustainable in pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…There has been an increased in the use of non-drugs treatment for the participants in our study. A systematic review from Tang et al (24). suggests that non-pharmacological interventions are suitable and sustainable in pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…Campo, et al [134] found that levels of fatigue and distress in senior prostate cancer survivors that were enrolled in a 12-week randomized controlled trial. Kinney, et al [135] found that tai chi qigong promotes recovery from prostate cancer. They combined various qigong movements with simplified tai chi movements, such as Tai Chi Ruler [136], Cloud Hands [137][138][139] and Wild Goose [140].…”
Section: Prostate Cancermentioning
confidence: 99%
“…2021 percebe-se que a pele não tem a mesma firmeza, o corpo perde a elasticidade e as memórias começam a falhar, junto disso as doenças crônicas como o diabetes e a hipertensão arterial se manifestam e, a dor comumente ocorre. Trauma, lesões e doenças podem causar dor em idosos (TANG et al, 2019).…”
Section: Referencial Teóricounclassified
“…Comumente na fase idosa ocorre a utilização de vários medicamentos, também designado poli farmácia, que inclusive podem interagir entre si e trazer prejuízo ao idoso. O uso de anti-inflamatórios não esteroides é o método mais comum de alívio da dor em idosos devido à sua eficácia, porém pode ocasionar sangramento gastrointestinal, oligúria, retenção de líquidos, diminuição da excreção de sódio, insuficiência renal e sangramento prolongado (TANG et al, 2019).…”
Section: Referencial Teóricounclassified